Strategi Perencanaan dan Pengembangan Sumber Daya Manusia untuk Meningkatkan Daya Saing Organisasi - Setia Ningsih, Sandra Nurfadila; Putri, Agustina Mulia (UNIVERSITAS SERAMBI MEKKAH, 2025)
Human resource planning and development (HRD) are critical factors in enhancing organizational competitiveness, particularly at PT ABC Elektronik Indonesia. This study aims to explore the human resource planning and development strategies implemented by the company to improve productivity and organizational performance. The research used a qualitative method with structured interviews and document analysis. The results indicate that data-driven HR planning and the use of digital technology successfully increased productivity by 18% and efficiency by 12% in the production line. Furthermore, competency-based training, mentoring, and coaching improved employee satisfaction and retention. Challenges faced include resistance to technology and skill gaps among employees. Recommendations include a collaborative approach, phased training, and periodic evaluations to improve HR strategy implementation. With the right strategy, PT ABC Elektronik Indonesia can continue to strengthen its competitiveness in the era of Industry 4.0.